2002
DOI: 10.3168/jds.s0022-0302(02)74409-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress Responses during Milking; Comparing Conventional and Automatic Milking in Primiparous Dairy Cows

Abstract: A comparative study was performed to evaluate the differences in behavioral and physiological stress responses during milking between cows that were milked by an automated milking system (AM-cows) and cows that were milked in a conventional tandem parlor (TM-cows). In a randomized design, 36 primiparous Holstein-Friesian dairy cows were observed and blood sampled (1-min intervals) individually during milking. AM-cows spent less time standing with their heads outside the feeding trough than TM-cows and had a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
65
3
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 24 publications
13
65
3
3
Order By: Relevance
“…Earlier studies found elevated (Gygax et al, 2008) or similar (Hagen et al, 2005) HR during lying posture in AMS compared to conventional milking systems; however, both studies reported on higher basal sympathetic tone in AMS. Hopster et al (2002) found no difference between HR and HRV measured during standing in the barn in either parlour or robotic milking systems. We suppose that stress related to the procedure of milking in the conventional system is acute, considering that between two milkings the cows are left undisturbed in the barn, without human presence, free to rest or perform their daily activities, just as in the robotic milking system.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Earlier studies found elevated (Gygax et al, 2008) or similar (Hagen et al, 2005) HR during lying posture in AMS compared to conventional milking systems; however, both studies reported on higher basal sympathetic tone in AMS. Hopster et al (2002) found no difference between HR and HRV measured during standing in the barn in either parlour or robotic milking systems. We suppose that stress related to the procedure of milking in the conventional system is acute, considering that between two milkings the cows are left undisturbed in the barn, without human presence, free to rest or perform their daily activities, just as in the robotic milking system.…”
Section: Discussionmentioning
confidence: 61%
“…AUCs calculated for HR, frequency domain and Poincaré measures of HRV indicated lower vagal and higher sympathetic activity in parlour milking. Hopster et al (2002) also reported lower HR in the waiting area in AMS, compared to PARL. Stress was presumably a result of aversive handling methods (Pajor et al, 2000) or crowding in the holding area (Morgan and Tromborg, 2007;Kovács et al, 2013).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations